2009
DOI: 10.1194/jlr.r800027-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient supplements and cardiovascular disease: a heartbreaking story

Abstract: Observational data have identified associations between carotenoids, folic acid, and vitamin E, or metabolites altered by these nutrients, and cardiovascular disease (CVD) risk. Despite biological plausibility, for the most part, data derived from nutrient supplement trials using moderate to high doses of single nutrients or nutrient combinations (exceeding amounts to avoid nutrient deficiency) have been disappointing. The data for vitamin D is not yet adequate to evaluate; observational data suggest were a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 69 publications
0
19
0
1
Order By: Relevance
“…192 In a handful of crosssectional studies with adults, depression has been associated with reduced levels of micronutrients and their metabolites, some of which may be relevant to CVD. 193,194 Disparities in zinc, folate, and vitamins D and E have been reported between depressed and nondepressed adults, 195,196 although as a whole, the findings have been inconsistent and constrained by methodological limitations. 197 In a recent meta-analysis, there were significantly lower blood zinc concentrations among depressed adults (n=1642) than among control subjects (n=804).…”
Section: Nutritionmentioning
confidence: 99%
“…192 In a handful of crosssectional studies with adults, depression has been associated with reduced levels of micronutrients and their metabolites, some of which may be relevant to CVD. 193,194 Disparities in zinc, folate, and vitamins D and E have been reported between depressed and nondepressed adults, 195,196 although as a whole, the findings have been inconsistent and constrained by methodological limitations. 197 In a recent meta-analysis, there were significantly lower blood zinc concentrations among depressed adults (n=1642) than among control subjects (n=804).…”
Section: Nutritionmentioning
confidence: 99%
“…These examples indicate that although folic acid has beneficial effects in specific physiological contexts – i.e. during pregnancy when it effectively lowers the incidence of birth defects – it might induce adverse effects in the human population as indeed suggested by published CVD risk studies [66,67]. Effects on DNA methylation at yet unidentified loci are likely to underlie at least part of these outcomes.…”
Section: Diet Dna Methylation and Atherosclerosis Risk: The New Chalmentioning
confidence: 97%
“…Recent articles review the conclusions of several studies conducted on the topic [67,68]. Adverse effects might be due to widespread epigenetic changes, as recent work showed that vitamin C elicits global DNA hypomethylation in human embryonic stem cells [69].…”
Section: Diet Dna Methylation and Atherosclerosis Risk: The New Chalmentioning
confidence: 99%
“…In brief, Mensink noted that prospective cohort studies and randomized controlled trials can be complementary or contradictory [28] , as illustrated by studies on antioxidants [29] , folic acid [30] and possibly SAFA [31] . He emphasized the importance of discussing the replacement nutrient(s) when SAFA intake is reduced, and observed that a food pattern or food is more than a single nutrient.…”
Section: Should Saturated Fat Intakes Be Reduced?mentioning
confidence: 99%